2019
DOI: 10.1111/all.13699
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐phenotype correlations in Brazilian patients with hereditary angioedema due to C1 inhibitor deficiency

Abstract: et al. A new approach to the isolation and characterization of wheat flour allergens. Clin Exp Allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
0
13
0
4
Order By: Relevance
“…Several reasons for SERPING1 allelic heterogeneity have been developed by Germenis and Speletas (). A deeper knowledge of transcriptome signatures (López‐Lera, Cabo, Garrido, Dopazo, & López‐Trascasa, ) is expected to be gained in the coming years, with a contribution of epigenetic elements, gene–gene or gene–environment that regulate gene expression and biological processes, as recently suggested by Maia et al (). This important issue will lead to a better understanding of C1‐INH‐HAE pathophysiology and interpretation of genetics of C1‐INH‐HAE.…”
Section: Discussionmentioning
confidence: 92%
“…Several reasons for SERPING1 allelic heterogeneity have been developed by Germenis and Speletas (). A deeper knowledge of transcriptome signatures (López‐Lera, Cabo, Garrido, Dopazo, & López‐Trascasa, ) is expected to be gained in the coming years, with a contribution of epigenetic elements, gene–gene or gene–environment that regulate gene expression and biological processes, as recently suggested by Maia et al (). This important issue will lead to a better understanding of C1‐INH‐HAE pathophysiology and interpretation of genetics of C1‐INH‐HAE.…”
Section: Discussionmentioning
confidence: 92%
“…PCR was conducted using specific SERPING1 primers to amplify the 8 exons and intronic boundaries. Primer sequences and PCR conditions were as described by Maia et al [10]. DNA sequences were analyzed using Seqman software TM (Lasergene; DNAStar, Inc., Madison, WI, USA), with the SERPING1 gene sequence obtained from GenBank as a reference [10].…”
Section: Genetic Analysismentioning
confidence: 99%
“…Other important clues to differentiate them include the later onset of symptoms in AAE-C1-INH in the fourth or fifth decade of life, although symptoms of AAE-C1-INH have been reported in patients younger than 40 years [8], and the onset of symptoms in HAE-C1-INH that may occur in patients older than 40 years [10,11]. A family history of the disease is present in most patients with HAE-C1-INH, although up to 25% of cases of HAE-C1-INH could result from de novo mutations in SERPING1 [10]. Low C1q levels were found in 70-80% of AAE-C1-INH patients, while they were normal in those with HAE-C1-INH [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…New mutations are being defined every day, original research is reported from around the world, and new techniques are applied, providing improved understanding of the disease. [34,37,38] Next-generation sequencing has been used to study the genotype in C1-INH-HAE, and it has revealed that most [34] Relevant studies from our country [39] have been conducted and heterozygous mutations have been described in the 7 th exon (p.Leu416X [c.1247T> A]) by Akoglu et al [40] and by Büyüköztürk et al [41] in the promoter region (CAAT box, c.−101A>G). Ozkars et al [42] reported c. 601A>T nonsense variant mutation in the SERPING1 gene in C1-INH HAE patients.…”
Section: Serping1 Genementioning
confidence: 99%
“…[43,44] Genotype-phenotype correlations in C1-INH-HAE disease are currently being extensively investigated. [38,45,46] Speletas et al [45] conducted research in various European countries (Greece, Germany, Romania, and Hungary) and found that abdominal attacks were less common in Hungarians, and that the onset of the C1-INH-HAE type of the disease was delayed in Romanian patients.…”
Section: Serping1 Genementioning
confidence: 99%